Essential Oils from Residual Foliage of Forest Tree and Shrub Species: Yield and Antioxidant Capacity - Irene Mediavilla; Eva Guillamón; Alex Ruiz; Luis Saúl Esteban (Molecules, 2021)
Increasing applications and markets for essential oils could bring new opportunities for cost-effective and sustainable management of unused forestry biomass; however, better knowledge of the production and application of such essential oils is necessary. The objective of this work is to contribute to greater knowledge of the essential oil production on a pilot scale from foliage biomass of wild shrubs and tree residues produced in some forestry enhancement operations and to study their antioxidant capacity (ORAC—oxygen radical absorbance capacity). Fresh biomass (twigs) of seven species (E. globulus, E. nitens, P. pinaster, P. sylvestris, R. officinalis, C. ladanifer, and J. communis) was manually collected in Spain in two different periods and was ground at 30 mm and distilled in a 30 L stainless steel still with saturated steam. The essential oil components were identified by GC–MS and quantified by GC–FID, and their antioxidant activity was determined with the ORAC method. Promising results on essential oil yield were obtained with E. globulus, E. nitens, R. officinalis, and J. communis. All essential oils studied exhibited antioxidant capacity by the ORAC assay, particularly that from C. ladanifer. Moreover, oxygenated sesquiterpenes contents, one of the minor components of oils, were significantly correlated with ORAC values.